Tax Risk Management in Corporate Mergers: A Normative Assessment of Legal Certainty and Anti-Avoidance Risks in Indonesian Tax Law - Yoyo Arifardhani; Theresia Magdalena (Universitas Muhammadiyah Surabaya, 2026)
Corporate mergers as a strategy for business expansion generate complex tax implications, particularly regarding the transfer of assets and liabilities and changes in corporate organizational structures that may affect the tax base. In Indonesia, although various tax regulations governing merger transactions have been enacted, legal uncertainty persists and creates significant tax risks if such transactions are not carefully structured. These risks may arise in relation to income tax, value-added tax, and land and building acquisition duties, potentially increasing the tax burden and triggering disputes with tax authorities. This study aims to analyze the legal and regulatory framework governing corporate merger taxation in Indonesia, identify potential tax risks embedded in the regulatory structure and transactional practices, and determine effective strategies for mitigating such risks. This research employs a normative juridical method using statutory, conceptual, and comparative approaches. The analysis examines key Indonesian tax regulations, including the Income Tax Law, the Value Added Tax Law, and regulatory provisions governing corporate restructuring, supported by relevant academic literature and legal materials. The findings indicate that tax risks in merger transactions can be mitigated through the strategic use of specific legal instruments within the Indonesian tax framework. In particular, the application of tax-neutral merger provisions, the utilization of restructuring tax facilities, and the implementation of comprehensive tax due diligence prior to the transaction are identified as the most effective mitigation strategies. These mechanisms help ensure regulatory compliance while minimizing potential tax disputes. However, interpretative gaps and enforcement inconsistencies in anti-avoidance provisions continue to generate legal uncertainty, highlighting the need for clearer regulatory guidance to strengthen legal certainty in corporate merger taxation.